1988
DOI: 10.1063/1.99572
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse scattering and superstructure reflections from In1−y(AlxGa1−x)yP

Abstract: The structure of In1−y (Alx Ga1−x )y P semiconductor alloy systems was studied by electron diffraction. Varied distribution of diffuse scattering and superstructure reflections was observed. The pertinent ordered structure is dependent on growth parameters, but not on the alloy systems. The diffuse scattering could be attributed to mean square atomic displacements due to the coexistence of different column III atoms in the same sublattice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Yasuami et al 10 investigating OMVPE GaInP layers showed diffuse scattering at ~ 1 2 { 110} positions in a GaInP layer grown at 650°C. 2a and 2b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yasuami et al 10 investigating OMVPE GaInP layers showed diffuse scattering at ~ 1 2 { 110} positions in a GaInP layer grown at 650°C. 2a and 2b.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The successful growth of 0.98 µm lasers using GaInP cladding layers has been achieved by chemical beam epitaxy (CBE), 3 although the alloy layers have been commonly grown by organometallic vapor phase epitaxy (OMVPE). [5][6][7][8][9][10][11][12][13][14][15][16] Energy calculations have predicted that the CuPt-type ordering can result in a significant reduction in the bandgap energy 17 and experimental measurements have shown this to be the case for OMVPE GaInP and GaInAs layers. [5][6][7][8][9][10][11][12][13][14][15][16] Energy calculations have predicted that the CuPt-type ordering can result in a significant reduction in the bandgap energy 17 and experimental measurements have shown this to be the case for OMVPE GaInP and GaInAs layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples used in this study were essentially the same as those used in previous work (Yasuami, Nozaki & Ohba, 1988;Nozaki, Ohba, Sugawara, Yasuami & Nakanisi, 1988). Ino.sGao.sP and Ino.sAlo.sP, expitaxic layers were grown by OMVPE on (001) GaAs substrates.…”
Section: Methodsmentioning
confidence: 99%
“…1987), InxGal-~,P (Gomyo, Suzuki, Kobayashi, Kawata, Hino & Yuasa, 1987;Ueda, Takikawa, Komeno & Umebu, 1987;Bellon, Chevalier, Martin, Dupont-Nivet, Thiebaut & Andr6, 1988;McKernan, DeCooman, Carter, Bour & Shealy, 1988;Gomyo, Suzuki & Iijima, 1988;Dabkowski, Gavrilovic, Meehan, Stutius, Williams, Shahid & Mahajan, 1988;Kondow, Kakibayashi & Minagawa, 1988) and Inx(Ga~.All-y)l-~P (Yasuami, Nozaki & Ohba, 1988;Gavrilovic, Dabkowski, Meehan, Williams, Stutius, Hsieh, Holonyak, Shahid & Mahajan, 1988). The investigation of Inx(GayAll_y)l_xP grown on a (001) GaAs substrate by OMVPE was motivated by reports of an unexpected bandgap variation which depends on the growth temperature and the V/III molar ratio in the gas composition (Ohba, Ishikawa, Sugawara, Yamamoto & Nakanisi, 1986;Gomyo, Kobayashi, Kawata, Hino, Suzuki & Yuasa, 1986 (Suzuki, Gomyo & Iijima, 1988;Bellon, Chevalier, Augarde, Andr6 & Martin, 1989).…”
Section: Introductionmentioning
confidence: 99%